The Existence of Augmented Reality in Mathematics Learning: A Systematic Literature Review - Angraini, Lilis Marina; Rahmawati (Department of Mathematics, Universitas Negeri Padang (UNP), 2024)
Augmented reality (A.R.) represents cutting-edge technology bridging digital information with the real world. In the context of learning, particularly concerning augmented reality, researchers, educators, and practitioners face the imperative of adapting to the challenges posed by this digital era. This systematic literature review aims to comprehensively explore and contrast multiple articles indexed in the Scopus Database, focusing on the intersection of mathematics education and Augmented Reality. The analysis underscores that A.R. presents a promising tool for heightening engagement and comprehension of mathematical concepts, particularly emphasized in elementary education and centered around matrices/geometry topics. The outcomes carry substantial implications for educators, advocating for the incorporation of A.R. as an innovative teaching method in mathematics and policymakers, signaling the necessity to foster the integration of A.R. technology in educational settings. Furthermore, this study's implications offer valuable direction for future research endeavors, suggesting the need for a more comprehensive exploration of specific facets of using A.R. in mathematics education.